MENJADIKAN PESANTREN SEBAGAI PUSAT PERADABAN MUSLIM DI INDONESIA - Imam Mustofa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
This article discusses three main problems are related to the preparation of boarding schools (pesantren) to become the center of Muslim civilization in the global era. Firstly, it is releated to the existence of pesantren in Indonesia. Secondly, deals with opportunities and challenges of pesantren to become center of civilization in the global era. Thirdly, these things must be prepared by pesantren to be the center of Muslim civilization. Study in this article is the normative descriptive analysis which is result of in-depth review of the literature related with pesantren and civilization. Historical facts show and proved that until now pesantren can still exist as a place of education for society and survived, even able to keep rhythm of turnaround of time. There is tremendous opportunity to make pesantren as a center of Muslim Civilization in Indonesia in the global era. However, there are many challenges too. Therefore, it is necessary preparations of the pesantren to capture these opportunities and overcome all challenges. These Preparations are, laid of core or foundation of civilizations, development paradigm of thinking civitas of pesantren, mastery and development of modern science and development of higher education institution of pesantren (ma'had Aly).